Simulation-based education as a tool for enhancing the quality of medical education - Akilbekov Dzhumatovich; Elnaz Salimrouhi (Journal of Preventive and Complementary Medicine)
Simulation-based education (SBE) has emerged as a transformative tool in medical training, offering a safe and controlled environment for learners to acquire and refine essential clinical skills. Initially confined to basic role-playing and the use of standardized patients, SBE has rapidly evolved with the incorporation of advanced technologies such as virtual reality (VR), augmented reality (AR), and artificial intelligence (AI)-driven simulations. These innovations enable medical students to engage in high-fidelity scenarios that closely replicate complex, real-world clinical situations, thereby providing an immersive learning experience. SBE is particularly effective in enhancing clinical competence, improving decision-making abilities, reducing medical errors, and promoting patient safety. By bridging the gap between theoretical knowledge and practical application, SBE ensures that learners are better equipped to face real-life challenges in healthcare settings.Despite its evident advantages, SBE encounters several challenges that impede its widespread adoption. Key issues include the high costs associated with simulation technologies, the necessity for ongoing technical support and maintenance, and the requirement for trained faculty to effectively guide and assess students. Additionally, while many simulation models strive for realism, some still do not fully capture the complexities of real-world clinical environments, which can limit their applicability to actual patient care.Nevertheless, numerous successful case studies highlight the effectiveness of SBE in enhancing medical education. Various institutions have successfully integrated simulation into their curricula, employing best practices for skill development, assessment, and interprofessional education. The future of SBE appears promising, with emerging technologies such as AI, VR, and gamification set to broaden its scope and impact. Further research is essential to understand the long-term effects of SBE on medical education and healthcare outcomes, as well as to identify strategies for making simulation more cost-effective and sustainable.